Wave Climate Variations in Indonesia Based on ERA-Interim Reanalysis Data from 1980 to 2014. - Zikra, Muhammad; Ashfar, Putika (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
In this study, temporal variation in significant wave height are studied using ERA-Interim reanalysis data from ECMWF (European Centre for Medium-Range Weather Forecasts) for 35 years period from 1980-2014. The ERA-Interim reanalysis data provides wind speed and wave height data with resolution of 1 x 1 degree. This paper studied monthly variation in significant wave height and wind speed by creating monthly data and taking the mean of those months over a period 35 years. The results show that the mean wind speed and significant wave height in the South of Java Sea have an increasing trend for all month.